Multivariate analysis of a geopolymeric system containing metakaolin and α-Al2O3. (13th June 2023) - da Costa, Danúbia Lisbôa; da Costa, Fabiana Pereira; Fernandes, Jucielle Veras; Pinto, Haroldo Cavalcanti; Cartaxo, Juliana de Melo; Neves, Gelmires de Araújo; Menezes, Romualdo Rodrigues; Rodrigues, Alisson Mendes
Highlights: MK-based geopolymers containing metakaolin and α-Al2 O3 . Multi-variational analysis of α-Al2 O3 content on flexural strength of geopolymers. Multi-variational analysis of temperature on flexural strength of geopolymers. 2x2 factorial experimental design, with star point, duplicated at the central point. Mathematical models to describe the effect of the temperature and curing conditions. Abstract: Geopolymer materials are a promising and eco-friendly alternative to Portland cement. This work investigates the combined effect of α-alumina (α-Al2 O3 ) content, temperature, and curing conditions on the mechanical properties of metakaolin-based geopolymers containing α-Al2 O3 . The influence of α-Al2 O3 content and curing temperature (Tc ) were evaluated using a central composite design. The geopolymers were developed from metakaolin/α-Al2 O3 mixtures activated with a NaOH solution, uniaxially pressed (33 MPa/30 s), and cured at the experimental design temperatures under different conditions: i) curing for 24 h; ii) pre-curing at room temperature for 24 h and curing for 24 h and iii) pre-curing for 24 h and curing for 48 h. Statistical analyzes were performed to evaluate the variables' significance (α-Al2 O3 content and Tc ) and their interactions. Response surfaces modeling and mathematical models were described to predict the flexural strength values as a function of each curing condition. The results showed that temperature and curing time has an essential role in the flexural strength (σf ), with the temperature being a significant factor in all experimental conditions evaluated. Inserting a pre-curing step at room temperature for 24 h favored the increase in σf values. Furthermore, regardless of the % α-Al2 O3, the σf for samples with pre-curing did not vary significantly with the curing time.